Radiographic and α-fetoprotein response predict pathologic complete response to immunotherapy plus a TKI in hepatocellular carcinoma: a multicenter study - Cheng Huang; Xiao-Dong Zhu; Ying-Hao Shen; Bin Xu; Dong Wu; Yuan Ji; Ling-Li Chen; Tian-Qiang Song; Wei Zhang; Zhi-Ming Zeng; Hua-Sheng Huang; Kui Wang; et al. (BMC Cancer, 2023)
Abstract Background Pathologic complete response (pCR) following preoperative systemic therapy is associated with improved outcomes after subsequent liver transplant/resection in hepatocellular carcinoma (HCC). However, the relationship between radiographic and histopathological response remains unclear. Methods We retrospectively examined patients with initially unresectable HCC who received tyrosine kinase inhibitor (TKI) plus anti–programmed death 1 (PD-1) therapy before undergoing liver resection between March 2019 and September 2021 across 7 hospitals in China. Radiographic response was evaluated using mRECIST. A pCR was defined as no viable tumor cells in resected samples. Results We included 35 eligible patients, of whom 15 (42.9%) achieved pCR after systemic therapy. After a median follow-up of 13.2 months, tumors recurred in 8 non-pCR and 1 pCR patient. Before resection, there were 6 complete responses, 24 partial responses, 4 stable disease cases, and 1 progressive disease case, per mRECIST. Predicting pCR by radiographic response yielded an area under the receiver operating characteristic curve (AUC) of 0.727 (95% CI: 0.558–0.902), with an optimal cutoff value of 80% reduction in the enhanced area in MRI (called major radiographic response), which had a 66.7% sensitivity, 85.0% specificity, and a 77.1% diagnostic accuracy. When radiographic response was combined with α-fetoprotein response, the AUC was 0.926 (95% CI: 0.785–0.999); the optimal cutoff value was 0.446, which had a 91.7% sensitivity, 84.6%, specificity, and an 88.0% diagnostic accuracy. Conclusions In patients with unresectable HCC receiving combined TKI/anti–PD 1 therapy, major radiographic response alone or combined with α-fetoprotein response may predict pCR.